Disentangling ecologically equivalent from neutral species: The mechanisms of population regulation matter. Issue 11 (31st July 2019) - McPeek, Mark A.; Siepielski, Adam M.
Abstract: The neutral theory of biodiversity explored the structure of a community of ecologically equivalent species. Such species are expected to display community drift dynamics analogous to neutral alleles undergoing genetic drift. While entire communities of species are not ecologically equivalent, recent field experiments have documented the existence of guilds of such neutral species embedded in real food webs. What demographic outcomes of the interactions within and between species in these guilds are expected to produce ecological drift versus coexistence remains unclear. To address this issue, and guide empirical testing, we consider models of a guild of ecologically equivalent competitors feeding on a single resource to explore when community drift should manifest. We show that community drift dynamics only emerge when the density‐dependent effects of each species on itself are identical to its density‐dependent effects on every other guild member. In contrast, if each guild member directly limits itself more than it limits the abundance of other guild members, all species in the guild are coexisting, even though they all are ecologically equivalent with respect to their interactions with species outside the guild (i.e. resources, predators, mutualists). Hence, considering only interspecific ecological differences generating density dependence, and not fully accounting for the preponderance of mechanisms causing intraspecific density dependence, will provide an incomplete picture for segregating between neutrality and coexistence. We also identify critical experiments necessary to disentangle guilds of ecologically equivalent species from those experiencing ecological drift, as well as provide an overview of ways of incorporating a mechanistic basis into studies of species coexistence and neutrality. Identifying these characteristics, and the mechanistic basis underlying community structure, is not merely an exercise in clarifying the semantics of coexistence and neutral theories, but rather reflects key differences that must exist among community members in order to determine how and why communities are structured. Abstract : What demographic outcomes of interactions within and between species guilds are expected to produce ecological drift versus coexistence remains unclear. To address this issue, and guide empirical testing, the authors consider models of a guild of ecologically equivalent competitors feeding on a single resource to explore when community drift should manifest. Results from these models illustrate the need for a more mechanistic understanding of the processes underlying community structure.